Analysis of unsymmetrical fault - Firdaus Johan
This project is to analyzed of unsymmetrical fault with using the software named Mi Power. In this case of the project we should identify types of fault when fault occurred whether they are Single Line To Ground, Line To Line, and Double Line To Ground Fault.